Too much or too little? Price-discrimination in a market for credence goods - Uwe Dulleck; Rudolf Kerschbamer; Alexander Konovalov (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
In markets for credence goods sellers are better informed than their customers about the quality that yields the highest surplus from trade. This paper studies second-degree price-discrimination in such markets. It shows that discrimination regards the amount of advice offered to customers and that it leads to a different distortion depending on the main source of heterogeneity among consumers. If the heterogeneity is mainly in the expected cost of efficient service, the distortion involves overprovision of quality. By contrast, if consumers differ mainly in the surplus generated whenever the consumer's needs are met, the inefficiency involves underprovision of quality.
Keywords: L15; D82; D40; 330; Price Discrimination; Credence Goods; Experts; Discounters; Distribution Channels